2010
DOI: 10.1007/s00436-010-2036-2
|View full text |Cite
|
Sign up to set email alerts
|

Horses naturally infected by Trypanosoma vivax in southern Brazil

Abstract: In this study, we reported the first outbreak of the infection by Trypanosoma vivax in horses in southern Brazil, a non-endemic region where bovines have only recently been found infected by this trypanosome species. We evaluated 12 horses from a farm in southern Brazil, where four horses displayed pale mucous membranes, fever, weight loss, and swelling of abdomen, prepuce, or vulva. The diagnosis of T. vivax was confirmed in four horses by morphological parameters of trypomastigotes in blood smears and specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…However, in non-endemic areas, including Northeastern and Southeastern Brazil, where herds are immunologically naïve in relation to this hemoprotozoan, T. vivax has become a primary agent and can cause wasting disease and high levels of mortality (BATISTA et al, 2007DA SILVA et al, 2011). All of the abovementioned factors probably contributed towards increasing the rate of T. vivax transmission and were triggering factors for outbreak that we reported in this study.…”
Section: Outbreak Characterization and Clinical Signsmentioning
confidence: 72%
See 4 more Smart Citations
“…However, in non-endemic areas, including Northeastern and Southeastern Brazil, where herds are immunologically naïve in relation to this hemoprotozoan, T. vivax has become a primary agent and can cause wasting disease and high levels of mortality (BATISTA et al, 2007DA SILVA et al, 2011). All of the abovementioned factors probably contributed towards increasing the rate of T. vivax transmission and were triggering factors for outbreak that we reported in this study.…”
Section: Outbreak Characterization and Clinical Signsmentioning
confidence: 72%
“…This showed a 177 bp amplified DNA fragment, which confirmed the diagnosis of T. vivax infection (CORTEZ et al, 2009). Analyses on CatL-amplified sequences indicated that there was high genetic similarity among T. vivax isolates from Northern, Central and Southern Brazil that have been found circulating in cattle, water buffaloes, sheep, goats and horses (CORTEZ et al 2006(CORTEZ et al , 2009DA SILVA et al, 2011).…”
Section: Pcr Techniquementioning
confidence: 99%
See 3 more Smart Citations